Demographics and Histopathological Patterns of Oral Squamous Cell Carcinoma at a Tertiary Level Referral Hospital in Hyderabad, India: A 5-Year Retrospective Study - Kiran, G; Shyam, NDVN; Rao, Jagadeeshwar; Krishna, A; Reddy, B Sridhar; Prasad, N (Journal of Orofacial Research, 2012)
Background: To study the demographics and histopathological patterns of oral squamous cell carcinoma (OSCC) reported at a tertiary level referral teaching hospital in Hyderabad, India. Materials and methods: An institutional retrospective study of biopsies sent to a tertiary level referral teaching hospital, Hyderabad. The data was collected year-wise for a period of 5 years from 2007 to 2011 with reference to age, sex, site involved and final diagnosis based on the histopathological findings. Results: A total of 1,005 oral biopsies were reviewed. Of these, OSCC was seen in 234 cases (23.28%). Buccal mucosa (47.7%) was the most frequently involved site followed by tongue (27.6%). Most of the OSCC patients were in the age group of 41 to 50 years, males and histopathologically well-differentiated (62%). Conclusion: This study showed that OSCC is widespread in the patients of this region.